A champagne tower of influence: An interview study of how corporate boards enact occupational health and safety. (November 2021) - Lornudd, Caroline; Frykman, Mandus; Stenfors, Terese; Ebbevi, David; Hasson, Henna; Sundberg, Carl Johan; von Thiele Schwarz, Ulrica
Highlights: A unique view on strategic health and safety from within the boardroom. Multiple examples of concrete governance actions described by board members. The board room is a social arena, impacting the chief executive officer's priorities. The board has an agenda-setting role, besides a controlling and an empowering role. Abstract: The board of directors is responsible for governing organizations, including firms' occupational health and safety (OHS). However, empirical research addressing how boards of directors enact OHS responsibility is scarce. In this study, we explored how boards of directors describe how their board acts to take responsibility for OHS. A secondary aim was to analyze whether those actions represent governance according to the agency theory and/or the stewardship theory. The empirical material consisted of 34 interviews with board members and chief executive officers in large private companies from four industries: trade, construction, manufacturing, and health/social care. Using Boardman and Lyon's framework for OHS governance, we conducted a hybrid thematic analysis. The findings deepen and broaden the current understanding of the role that the board of directors may play in OHS governance in private companies. The boards' actions for taking responsibility for OHS both represent governance in line with the agency theory and stewardship theory. However, the boards' actions also underpin a behavioral view of corporate OHS governance. This suggests an influence on the organization that starts with actions in the boardroom and, like champagne in a glass tower, trickles down from the executive directors to other layers of the organization.